STRATEGY OF THE REGIONAL FINANCIAL MANAGEMENT AGENCY IN INCREASING LAND AND BUILDING TAX REVENUE IN PEMATANGSIANTAR CITY, NORTH SUMATRA PROVINCE - Ricky Alexander Hadirian Situmeang; Dahyar Daraba; Anselmus Tan (Jurnal Scientia, 2023)
This research is entitled Regional Financial Management Strategy in Increasing Land and Building Tax Revenue in Pematangsiantar City, North Sumatra Province. This research is motivated by the problem of land and building tax revenues having the smallest percentage of achievement compared to other types of taxes. The research method used in the preparation of this thesis is a qualitative research method with a descriptive approach. Data obtained through data collection: observation, interviews and documentation. The results of this study indicate that the Regional Financial Management Agency shows that the factors influencing the strategy to increase the collection of land and building taxes include the mandate, vision and mission and the internal and external environment. Based on the SWOT, the strategy for increasing future land and building taxes can be carried out by utilizing advances in science and technology by using existing human resources, budgets and facilities and infrastructure, intensifying the implementation of training for tax and building tax collection officers, intensifying socialization about the importance of land and property taxes. building to informal and community leaders. Suggestions need to be studied in depth regarding the Strategy for Increasing Land and Building Tax Revenue. While practical suggestions need to add to the Mission of the Regional Financial Management Agency, recommend strategies for improving land and buildings to tax parties so that they can be taken into consideration for the preparation of the next Regional Financial Management Agency program.